Strategi Penerjemahan Kolokasi dalam Novel Ar-Raṣāṣah Lā Tazāl Fī Jaibī - Aeni, Prisilia Anghuril (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose- This article aims to identify and classify the types of locations in the novel Ar-Raṣāṣah Lā Tazāl Fī Jaibī by Ihsan Abdul Quddus and analyze the translation strategies used based on Peter Newmark's translation theory. This study seeks to explain how these strategies are applied to produce accurate translations that are culturally appropriate. Design/Methodology/Approach- The research used a qualitative descriptive approach with a focus on collocation translation. Data was obtained from the novel Ar-Raṣāṣah Lā Tazāl Fī Jaibī as the primary data source along with its translation into Indonesian. Analysis was carried out through the identification of collocations, classification of types, and determination of translation strategies used according to Newmark's categories. Findings— The results of the study show that there are three main strategies used in collocation translation, namely Cultural Equivalent, Literal Translation, and Functional Equivalent. The Cultural Equivalent strategy is chosen to preserve the cultural nuances inherent in the source language, while Literal Translation is used to maintain direct equivalence of meaning. The Functional Equivalent strategy appears to be applied to collocations that require functional equivalence in the target language. Research Limitation/Implications- This study is limited to one literary work, so its findings do not reflect the diversity of collocations in Arabic literary texts more broadly. Nevertheless, this study makes an important contribution to understanding the patterns of Arabic-Indonesian collocation translation and can serve as a reference for translators in facing the challenges of cultural differences and choosing the right strategy.